2011
DOI: 10.1016/j.ajpath.2011.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of GLTSCR2 in the DNA Damage Response

Abstract: The cellular DNA damage response (DDR) ensures genomic stability and protects against genotoxic stresses. Conversely, defects in the DDR contribute to genome instability, with the resulting accumulated genetic changes capable of inducing neoplastic transformation. Thus, DDR is central to both the mechanism of oncogenesis and cancer therapy. Specifically, DDR is accomplished via a complicated meshwork of evolutionary conserved proteins, including ATM, ATR, and phospho-H2AX (γH2AX). GLTSCR2 is a nucleolar protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…The induction of Myc in conditions of mitochondrial stress may serve an adaptive function of stimulating glucose uptake and glycolysis to compensate for the impairment of oxidative phosphorylation, while also attempting to restore mitochondrial activity. Previous studies have suggested that GLTSCR2 is induced by genotoxic stressors, such as ionizing radiation and UV radiation, and low-dose actinomycin D, which is thought to cause ribosomal stress by inhibiting rRNA synthesis (28,29). It is possible that some of these agents may also impinge upon mitochondrial function and activate pathways leading to the induction of GLTSCR2.…”
Section: Discussionmentioning
confidence: 99%
“…The induction of Myc in conditions of mitochondrial stress may serve an adaptive function of stimulating glucose uptake and glycolysis to compensate for the impairment of oxidative phosphorylation, while also attempting to restore mitochondrial activity. Previous studies have suggested that GLTSCR2 is induced by genotoxic stressors, such as ionizing radiation and UV radiation, and low-dose actinomycin D, which is thought to cause ribosomal stress by inhibiting rRNA synthesis (28,29). It is possible that some of these agents may also impinge upon mitochondrial function and activate pathways leading to the induction of GLTSCR2.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that GLTSCR2 was redistributed from the nucleolus to the nucleoplasm in response to ribosomal stresses, such as hypoxia or Act-D, and the interaction of GLTSCR2 with p53 increased in parallel with the nucleoplasmic mobilization of GLTSCR2 ( Figure 6). Together with our recent report that GLTSCR2 is translocated to the nucleoplasm in response to DNA damage, 39 this finding indicates that GLTSCR2 is a dynamic protein that shuttles between the nucleolus and nucleoplasm, similar to other p53-regulating nucleolar proteins such as NPM and NS. 8,12 Nucleolar proteins interact with each other to form intricate networks for the regulation of p53.…”
Section: Discussionmentioning
confidence: 89%
“…It has been reported that nucleolar stress induces nucleoplasmic translocation of both GLTSCR2 and ARF [15, 16]. Thus, to characterize the protein binding between GLTSCR2 and ARF under nucleolar stress, we performed PLAs in HeLa cells treated with actinomycin D (Act-D).…”
Section: Resultsmentioning
confidence: 99%
“…Although these findings indicate that GLTSCR2-ARF binding was crucial for nucleoplasmic ARF translocation, it was unclear how GLTSCR2-ARF binding in the nucleolus induced the nucleoplasmic translocation of ARF, rather than promoting its sequestration in the nucleolus. Thus, we hypothesized that ARF translocates in complex with GLTSCR2 when GLTSCR2 is released to the nucleoplasm, considering that GLTSCR2 shifts between the nucleolus and nucleoplasm in response to various cellular stresses [15]. To test this hypothesis, we examined whether ARF release from the nucleolus is induced when nucleoplasmic GLTSCR2 is increased by ectopic GLTSCR2 overexpression.…”
Section: Resultsmentioning
confidence: 99%